Forgotten Learners: High School Transition Students With Disabilities - Laughlin, Michael K. (Journal of Physical Education, Recreation and Dance, 2026)
Because physical literacy and activity are not emphasized in special education as they are in physical education or adapted physical education (PE/APE), this editorial explores two important questions: Do high school transition students receive PE/APE programming? And are PE/APE teachers introduced or exposed to transition services at any point in their teacher training?. © 2026 SHAPE America.
Keywords: dept.hms